PENGARUH PENDIDIKAN, PELATIHAN, DAN PRESTASI KERJA TERHADAP PENGEMBANGAN KARIER GURU TK DI KECAMATAN LASEM KABUPATEN REMBANG - Syabana, Nikmah; Nurhidayati, Anik (JAB (Jurnal Akuntansi & Bisnis), 2019)
This study aims to prove the effect of education, training and work performance on the career development of kindergarten teachers in Lasem District, Rembang Regency, both partially and together. The formulation of the problem in this study is how education, training, and work performance towards the career development of kindergarten teachers in Lasem District, Rembang Regency. The type of data in this study is subject data. The source of data in this study is primary data. The data collection technique in this study was a questionnaire using a Likert scale. The test instruments used by researchers are the reliability and validity tests. This study took a population of all kindergarten teachers in Lasem District with a total of 120 teachers. The number of samples in this study were 120 people and using saturated samples. The data analysis technique used in this study uses multiple linear regression analysis.The results showed that; (1) Education does not have a significant positive effect on career development, (2) Training has no significant positive effect on career development, (3) Work performance has a significant positive effect on career development, (4) Education, training, and work performance simultaneously has a positive positive effect significant. The results of the determination test (Adjusted R2) showed a value of 0.891 which means that the variables of education, training, and work performance could explain the career development variable of 89.1%. The remaining 10.9% is influenced by other factors outside the research model.Â Keywords : Education, Training, Job Performance, Career Development